Crimea and punishment: The impact of sanctions on Russian and European economies - Konstantin A. Cholodilin; Aleksei Netšunajev (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
The conflict between Russia and Ukraine that started in March 2014 resulted in bilateral economic sanctions imposed by Russia and Western countries, including the members of the euro area (EA). The paper investigates the impact of sanctions on the real side of the economy of Russia and the EA. Using an index that measures intensity of sanctions the effects of sanctions shocks are analyzed by the means of structural vector autoregression. The direct effect on GDP growth is documented for Russia but not for the EA. While, on average, 1.97% of the GDP quarter-on-quarter growth is estimated to be lost due to sanctions by Russia, the corresponding estimate for the aggregate EA is very small. On the contrary, the indirect effect through depreciation of the currency is shown to be more important for the EA.
Keywords: C32; F51; 330; political conflict; sanctions; economic growth; Russia; euro area; structural vector autoregression